2014
DOI: 10.1111/jnc.12701
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of striatal‐enriched tyrosine phosphatase 61 in the dorsomedial striatum is sufficient to increased ethanol consumption

Abstract: The STriatal-Enriched protein tyrosine Phosphatase 61 (STEP61) inhibits the activity of the tyrosine kinase Fyn and dephosphorylates the GluN2B subunit of the NMDA receptor, whereas PKA phosphorylation of STEP61 inhibits the activity of the phosphatase (Goebel-Goody et al. 2012). Previously, we found that ethanol activates Fyn in the dorsomedial striatum (DMS) leading to GluN2B phosphorylation, which, in turn, underlies the development of ethanol intake (Wang et al. 2010). Here, we tested the hypothesis that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 45 publications
2
55
1
Order By: Relevance
“…Indeed, excessive alcohol intake (20%IA2BC model) increases the interaction between FYN and PTPα, which in turn contributes to the sustained activation of the kinase 30 . Interestingly, alcohol-induced inhibition of STEP, as well as activation of FYN and PTPα, can be detected in the DMS but not in other striatal regions (that is, the dorsolateral striatum (DLS) and the NAc) 24, 29, 30, 32 , demonstrating that the molecular changes induced by alcohol intake are highly selective.…”
Section: Go Pathways Promote Excessive Drinkingmentioning
confidence: 96%
See 3 more Smart Citations
“…Indeed, excessive alcohol intake (20%IA2BC model) increases the interaction between FYN and PTPα, which in turn contributes to the sustained activation of the kinase 30 . Interestingly, alcohol-induced inhibition of STEP, as well as activation of FYN and PTPα, can be detected in the DMS but not in other striatal regions (that is, the dorsolateral striatum (DLS) and the NAc) 24, 29, 30, 32 , demonstrating that the molecular changes induced by alcohol intake are highly selective.…”
Section: Go Pathways Promote Excessive Drinkingmentioning
confidence: 96%
“…1), and the inhibition of A2ARs reduces alcohol consumption in rats in a moderate alcohol consumption model (10%OSA paradigm) 22, 23 . Alcohol-induced activation of PKA leads to the phosphorylation of numerous PKA substrates, including the FYN kinase inhibitor, striatum-enriched protein-tyrosine phosphatase (STEP; also known as PTPN5) 24 and RAS-specific guanine nucleotide-releasing factor 1 (RAS-GRF1) 25 . The consequences of these phosphorylation events are outlined below.…”
Section: Go Pathways Promote Excessive Drinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the answer to this question has not yet been fully investigated, it is likely that there is a differential regulation of STEP posttranslational modifications, depending on different brain regions. For example, phosphorylation of STEP 61 after alcohol consumption was described in the dorsomedial striatum but not in the nearby dorsolateral striatum or the nucleus accumbens (Darcq et al, 2014), while dephosphorylation of STEP 61 was reported within the hippocampus after alcohol consumption (Hicklin et al, 2011). The differential regulation of STEP is an open area of research in the biology of STEP and should provide additional insights into mechanisms by which disruption of STEP activity may give rise to one distinct disorder compared to another.…”
Section: Resultsmentioning
confidence: 99%